Theoretical model for measuring parameters of laser radiation - Курской, Ю.С. (Radiotekhnika, 2019)
The task of the work is creation of a theoretical model for measuring of the laser radiation parameter as a nonlinear dynamical system. The model provides for the measurement of the parameters in stationary and chaotic modes. The model can be used for ensuring the stability of the laser radiation parameters, and for controlling the chaotic radiation.